Fast Graphs of Statistical Distributions Using R - , Steven T. Garren (Archives of Current Research International, 2016)
When teaching elementary statistics courses, instructors may find themselves frequently drawing by hand the probability density functions of normal and t distributions. The author presents the R-package fastGraph, containing new functions in R, allowing graphs of probability density functions and cumulative distribution functions to be drawn on the computer with few keystrokes. These functions also allow shading under the curve of the probability density function to illustrate concepts such as p-values and critical values. An additional function which fits the line for simple linear regression is also introduced.